Socioeconomics of urban travel. Evidence from the 2001 NHTS. - Pucher, John; Renne, John L. (Eno Transportation Foundation, 2003)
The 2001 National Household Travel Survey (NHTS) confirms most of the same travel trends and variations among socioeconomic groups documented by its predecessors, the Nationwide Personal transportation Surveys (NPTS) of 1969, 1977, 1983, 1990, and 1995. The private car continues to dominate urban travel among every segment of the American population, including the poor, minorities, and the elderly. By comparison, public transport accounts for less than 2% of all urban travel. Even the lowest-income households make only 5% of their trips by transit. The most important difference in the 2001 NHTS is the doubling in modal share of walk trips in cities, due to a much improved survey technique that captured previously unreported walks. While the private car dominates travel, there are important variations in auto ownership and travel behavior by income, race, ethnicity, sex, and age. Overall, the poor, racial and ethnic minorities, and the elderly have much lower mobility rates than the general population. Moreover, the poor, blacks, and Hispanics are far more likely to use transit than other groups. Indeed, minorities and low-income households account for 63% of the nation s transit riders. Different socioeconomic groups also have different rates of carpooling, taxi use, bicycling, and walking. In addition, they travel different distances and at different times of day. Many of these socioeconomic variations in travel behavior have important consequences for public policy. difu
Keywords: Mobilität; Kraftfahrzeug; Stadtverkehr; Fahrradverkehr; Fußgängerverkehr; ÖPNV; Verkehrsmittelwahl; Verkehrsverhalten; Sozialstruktur; Bevölkerungsstruktur; Verkehrspolitik; Erhebung; Individualverkehr; Nichtmotorisierter Verkehr